Uncertainty Analysis of Flexural Overstrength Ratio for RC Columns - Aydemir, Cem; Zorbozan, Mustafa (ASCE-AMER SOC CIVIL ENGINEERS, 2012)
This paper summarizes the results of a comprehensive statistical study of the flexural overstrength ratio for estimation of the probable flexural strength of ductile RC columns with varying geometries and confinement levels. The material and section properties and the analytical model response are modeled as random variables and their effects on section behavior are assessed through statistical evaluation. For randomly sampled values of the considered variables, the sectional analyses are carried out using a computer program that uses various confined and unconfined concrete models to obtain the maximum flexural strength in the moment-curvature relationship. The effect of variability is investigated by examining the response distributions resulting from Monte Carlo simulations. Furthermore, a simple expression is derived for estimation of the probable flexural strength using the flexural overstrength ratio with the 10% probability of being exceeded. Finally, the proposed method is compared with ACI 318, Eurocode 8, and the Turkish seismic design code provisions. DOI: 10.1061/(ASCE)ST.1943-541X.0000528. (C) 2012 American Society of Civil Engineers.
Keywords: Probabilistic models; Reliability; Concrete columns; REINFORCED-CONCRETE COLUMNS; STATISTICAL-ANALYSIS; STRENGTH; CONFINEMENT; PERFORMANCE; DUCTILITY; CAPACITY; BEHAVIOR; MEMBERS; Construction & Building Technology; Engineering